3D-printed graphene-Al2O3 composites with complex mesoscale architecture. Issue 5 (1st April 2018) - Tubío, Carmen R.; Rama, Adrián; Gómez, Mónica; del Río, Fidel; Guitián, Francisco; Gil, Alvaro
Abstract: Composites of reduced graphene oxide (rGO) and Al2 O3 with complex three-dimensional (3D) mesoscale architecture were prepared by a combination of 3D printing technique and thermal reduction process. For this purpose, stable aqueous graphene oxide (GO) suspensions were prepared using GO sheets synthesized previously from graphite powders according to a modified Hummers method. The printability of the resulted inks was investigated by rheological tests under steady and dynamic shear conditions. GO-Al2 O3 structures with a 3D interconnected network were fabricated and thermally reduced in an N2 atmosphere. Finally, the reduction and distribution, as well as the integrity of rGO sheets in the ceramic matrix were evaluated using scanning electron microscopy (SEM), Raman spectroscopy, and X-ray diffraction (XRD) analysis. The reported 3D printed rGO-Al2 O3 composite offers a strategy for the fabrication of other graphene-ceramic composites with a high geometric surface area for a broad range of technological applications.